Vascular endothelial growth factor attenuates enhanced spontaneous transdifferentiation of classical and intermediate monocytes in patients with ischemic cardiomyopathy - M. V. Gladkovskaya; S. P. Chumakova; O. I. Urazova; V. S. Poletika; V. M. Shipulin; S. L. Andreev (Сеченовский вестник)
Aim. To evaluate the effect of vascular endothelial growth factor A (VEGF-A) on the subpopulation composition of monocytes in the blood mononuclear cell culture of patients with coronary heart disease (CHD), with and without ischemic cardiomyopathy (ICMP).Materials and methods. A single-center, experimental in vitro study was conducted. The study included 22 patients with CHD: 11 with ICMP, 11 without ICMP, and 10 healthy donors. Blood mononuclei were isolated from venous blood by immunomagnetic separation for CD14 and CD34 antigens, then incubated with and without the addition of VEGF-A 50 ng/mL (control and stimulated samples). After 6 days, the total monocyte content, the proportion of classical CD14++CD16–, intermediate CD14++CD16+, non-classical CD14+CD16++, and transitional CD14+CD16– monocytes were assessed using flow cytofluorimetry.Results. In groups of patients with CHD and in those groups where the patients were considered relatively healthy, a decrease in the content of CD14++CD16+ in the control and stimulated samples was shown. Only in the CHD group with ICMP relative to the control sample, after VEGF-A stimulation, a statistically significant increase in all CD14+ was found: 10.63% (6.80; 17.64) vs. 15.28% (8.75; 27.99), p < 0.01, and their subpopulations: CD14++CD16−: 6.08% (1.76; 8.84) vs. 8.57% (3.51; 16.8), p < 0.05, CD14++CD16+: 3.64% (2.03; 8.59) vs. 6.26% (3.87; 10.3), p < 0.05. In the same group, a tendency towards an increase in CD14+CD16++ was noted after stimulation: 0.19% (0.18; 1.11) vs. 0.61% (0.37; 1.58), p = 0.062. No differences in the content of all monocytes and their subpopulations after VEGF-A stimulation were found in the CHD without ICMP group nor in the healthy group. The content of CD14+CD16– in all groups in the control and stimulated samples did not differ.Conclusion. CHD is characterized by a deficiency of all CD14+ cells and intermediate monocytes due to their transdifferentiation. VEGF-A affects the subpopulation composition of monocytes in CHD only in the presence of ICMP by increasing the content of all CD14+ cells, and in their intermediate and classical forms without exceeding the indicators in healthy donors.